Penerapan Teori Operant Conditioning dalam Meningkatkan Motivasi dan Hasil Belajar Siswa SMP pada Kurikulum Merdeka - Aswar, Rifka Adriani; Suradi, Suradi; Danial, Danial (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze and synthesize various previous research findings regarding the application of Operant Conditioning theory to improve junior high school students' motivation and mathematics learning outcomes, as well as its relevance to the Independent Curriculum. The method used was library research with a qualitative descriptive approach to relevant scientific sources from the past ten years. The results indicate that the application of Operant Conditioning theory through reinforcement, particularly positive reinforcement, has a significant effect on improving students' motivation and mathematics learning outcomes. The more appropriate and consistent the reinforcement, the higher the students' motivation and engagement in the learning process, which impacts learning outcomes. Although the effectiveness of reinforcement implementation can vary depending on the learning context, student characteristics, and teacher strategies, Operant Conditioning theory remains a relevant approach for creating effective, meaningful mathematics learning that aligns with the principles of the Independent Curriculum. Keywords : Learning Outcomes, Independent Curriculum, Learning Motivation, Operant Conditioning, Mathematics Learning